Deposition of the 2011-2012 Cordõn Caulle tephra (Chile, 40S) in lake sediments: Implications for tephrochronology and volcanology - Bertrand, Sébastien; Daga, Romina Betiana; Bedert, Robin; Fontijn, Karen (Wiley Blackwell Publishing, Inc, 2014)
Fil: Bertrand, Sébastien. University of Ghent; Bélgica